PENGARUH TEKNOLOGI INFORMASI DAN KOMUNIKASI, JUMLAH PERUSAHAAN EKONOMI KREATIF, TENAGA KERJA EKONOMI KREATIF DAN NILAI EKSPOR EKONOMI KREATIF TERHADAP PDB EKONOMI KREATIF INDONESIA - Larissa Maria Margaretha (2022)
The purpose of this research is to analyze the effect of communication and information technology, number of creative economy industry, labor of creative economy, and creative economy exports on Indonesia's gross domestic product (GDP) in the 2013 - 2019 period. This research only use seven subsectors namely animated and video film, craft, culinary, music, fashion, publishing and fine art. This study use secondary data and the analytical method use panel data regression with the best approach, random effect model. The result of the study show that simultaneously the variables of communication and information technology, number of creative economy industry, labor of creative economy, and creative economy exports have a significant effect on the GDP of the creative economy for period 2013 - 2019. And partially the variables of communication and information technology and labor of creative economy have a significant effect on the GDP of the creative economy, but the variables of number of creative economy industry and creative economy exports do not have a significant effect on the GDP of the creative economy.